Drought and fires influence the respiratory diseases hospitalizations in the Amazon - Machado-Silva, Fausto; Libonati, Renata; Melo de Lima, Thiago Felipe; Bittencourt Peixoto, Roberta; de Almeida França, José Ricardo; de Avelar Figueiredo Mafra Magalhães, Mônica; Lemos Maia Santos, Filippe; Abrantes Rodrigues, Julia; DaCamara, Carlos C. (Ecological indicators, 2020)
•21st century respiratory morbidity in Amazon is linked to changes in rainfall regime.•Drought exerts a primary control increasing respiratory diseases, except for Asthma.•Fire season acts as secondary influence mainly increasing the number of Asthma.•Drought-fire compounded effect boosts respiratory illness in elderly and children. Precipitation decline and vegetation fires in the Amazon region associated with climate change and deforestation expose local communities to hazardous air quality that may lead to damages in human health such as diseases of the respiratory system. Since 2000, drought incidence over the Amazon has been observed at a higher frequency than during the last century, and the effects of the drier climate and fires on human health remain uncertain. Understanding the roles played by precipitation decline and fire activity as well as associated changes of atmospheric parameters on the incidence of respiratory diseases hospitalizations (RDH) is a very complex task, and it is likely that the relative importance of those factors depends on the temporal and spatial variability used in the analysis. This work aims at serving as an updated reference that covers the impact of fire incidence on respiratory diseases in Porto Velho, the third most populated city of Brazilian Amazon, with emphasis on drought events from 2000 to 2016. For this purpose, we compare remote sensing data, meteorological variables and health indicators, that include RDH, in particular for children under five years old (RDH5) and people aged more than sixty (RDH60), as well as Asthma and Bronchitis hospitalizations. Here we show an increase of 27% in RDH (except for Asthma that decreased 75%) in drought years as described by the positive (negative for Asthma) relationship with rainfall. Rainfall and humidity exert a primary control in diseases of the respiratory system in the region. Hotspots, burned areas and smoke concentrate in August and September, and have a secondary influence of fire on RDH. Smoke production is strongly related to fire and temperature, which are associated with an increase in the number of hospitalizations during the fire season. RDH5 and RDH60 are respectively 11 and 22 times higher than RDH (for all ages), confirming the higher vulnerability for children and elderlies. Based on the observed data, we highlight the role of regional precipitation trends in driving respiratory hospitalizations, which are crucial ecological indicators for humans in the context of climate change.